DESKRIPSI PERAN GURU DALAM PENANAMAN SIKAP ANTI BULLYING SISWA KELAS 4 DI SEKOLAH DASAR - Steven, Jordie Jhosua; Sofyan, Ahsan; Novitasari, Neni; Nenogasu, Novita Yusak (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2026)
This study aims to describe the role of teachers in instilling anti-bullying attitudes in fourth-grade students. The background of this study is based on the continued discovery of verbal and non-verbal bullying behavior in elementary school environments that impact students' comfort and psychological development. This study uses a qualitative descriptive method with one class teacher as the main subject and three students as supporting subjects. Data collection techniques were carried out through moderate participatory observation, open interviews, and documentation. Data analysis used an interactive model by Miles and Huberman which includes data reduction, data presentation, as well as drawing conclusions and verification, with validity testing through technical triangulation. The results of the study indicate that teachers have three main roles in instilling anti-bullying attitudes, namely as motivators, facilitators, and mediators. As motivators, teachers provide moral advice, character building, and foster empathy through stories and real-life examples. As facilitators, teachers create a safe, comfortable, and inclusive classroom atmosphere through role models, dialogue, and the use of educational media such as "Stop Bullying" posters. As mediators, teachers mediate conflicts, provide educational sanctions, and involve parents and school officials in certain cases. Overall, the role of teachers has proven to be very important in building a learning environment that is conducive, safe, and free from bullying behavior.